Factors Associated with the Clinical Severity and Disease Burden of COVID-19 Caused by Omicron BA.2 in Shanghai and Hong Kong, China - Ruijia Sun; Xinhua Chen; Yanpeng Wu; Hongjie Yu (Zoonoses)
Shanghai and Hong Kong, China, experienced an outbreak of COVID-19 in early 2022. Both cities had similar dynamic prevention policies and population-level immunity, but showed differences in the numbers of cases and deaths. We collected data from official websites to estimate and compare the infection rates, mortality rates, and infection fatality ratios (IFRs) between cities. We further performed univariable analysis and used two tree models to explore the factors affecting the differences. The infection rate in Hong Kong, China, was 42.45 (95% CI: 42.41–42.48) per 100 individuals (15.49 times higher than that in Shanghai). The mortality rate was 124.90 (95% CI: 122.33–127.46) per 100,000 individuals (51.61 times higher than that in Shanghai). The adjusted IFR was 0.29% (95% CI: 0.29–0.30%) (3.30 times higher than that in Shanghai). The infection rate was negatively correlated with the stringency of nonpharmaceutical interventions. The mortality rate and IFR negatively correlated with the vaccination rate. However, positive correlations were observed between the median age and both mortality and IFR, as well as between the proportion of people ≥65 and IFR. Overall, a lack of medical resources, lower vaccination rates, and higher median age were associated with a higher infection rate, mortality rate, and IFR in Hong Kong.